Stiffness of viroids and viroid-like RNA in solution. - Riesner, D (1982)
The sedimentation coefficients of the potato spindle tuber viroid, four viroid-like RNAs from cadang-cadang-disease, circular RNA from velvet tobacco mottle virus, circular RNA from Solanum nodiflorum mottle virus and double stranded RNA5 from cucumber mosaic virus were measured in the analytical ultracentrifuge. The numbers of nucleotides of the RNA species varied between 246 and 670. The hydrodynamic models of rigid rods and flexible cylinders were applied for the interpretation of the sedimentation coefficients. Double-stranded RNA5 from cucumber mosaic virus with 335 basepairs fits the model of a rigid rod with an hydrated diameter of 29 A. Potato spindle tuber viroid and the four viroid-like RNA species of cadang-cadang-disease form a homologous series of flexible cylinders with a Kuhn's statistical length lambda-1 of 600 A. The circular RNA from the two viruses mentioned above are more flexibel than the viroids and viroid-like RNAs. The hydrodynamic interpretation is in accordance with thermodynamic data and secondary structure models. In two of the RNAs from cadang-cadang, cruciform structures would also be possible on the basis of the nucleotide sequence. The hydrodynamic data, however, favour clearly the extended structure over the cruciform.